2016
DOI: 10.1002/ece3.1877
|View full text |Cite
|
Sign up to set email alerts
|

Pine invasions in treeless environments: dispersal overruns microsite heterogeneity

Abstract: Understanding biological invasions patterns and mechanisms is highly needed for forecasting and managing these processes and their negative impacts. At small scales, ecological processes driving plant invasions are expected to produce a spatially explicit pattern driven by propagule pressure and local ground heterogeneity. Our aim was to determine the interplay between the intensity of seed rain, using distance to a mature plantation as a proxy, and microsite heterogeneity in the spreading of Pinus contorta in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
1
20
1
Order By: Relevance
“…Further, our observed patterns stand in contrast to other studies of conifer regeneration, wherein density was one to two orders of magnitude greater during stand initiation [41,42]. Those studies found relatively simpler patterns and no effect of topography nor biotic interactions on those patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, our observed patterns stand in contrast to other studies of conifer regeneration, wherein density was one to two orders of magnitude greater during stand initiation [41,42]. Those studies found relatively simpler patterns and no effect of topography nor biotic interactions on those patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, seedling establishment outside plantations in Argentina was influenced more by seed density than by biotic or abiotic factors (Pauchard et al . ). Therefore, it is likely that where plantations can establish, non‐native pines can also invade.…”
Section: Discussionmentioning
confidence: 97%
“…Although non‐native pines grow across a range of abiotic conditions (Pauchard et al . ; Tomiolo et al . ), some native ecosystems are particularly vulnerable to invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of stand formation has important implications for tree invasion research as well as for invasion management. One implication is that space-for-time substitutions—commonly used in plant invasion research (Zenni et al 2014; Pauchard et al 2016)—cannot be applied at the stand scale, because all trees in the monodominant stand may be, on average, of similar age, so trees near the plantation’s edge are not necessarily older. Another significant outcome was the timing of invasion onset, which occurred ca.…”
Section: Discussionmentioning
confidence: 99%
“…For non-native species formation of monodominant stands is not clear, and for invasive conifers it has been proposed to occur as a gradual process from the seed source (e.g. encroaching a similar distance every year from the original source) (Zenni et al 2014; Pauchard et al 2016). Documenting the process of stand formation of non-native trees provides basic information, which allows formulating hypotheses regarding the causal mechanisms.…”
Section: Introductionmentioning
confidence: 99%